Reflections on Bullying in Costa Rica - Arias-Sandoval, Leonel (2018)
This essay aims to reflect on the social phenomenon of bullying in Costa Rica, a holistic approach that considers the various causes related to these acts of violence among peers. Bullying is a form of school violence; hence, it is difficult to give a single explanation of its causes as many factors can coexist and can make this phenomenon worse. Therefore, it follows that this is a complex and multi-causal social phenomenon and is part of a school culture that spreads in schools every day. It also has different manifestations: affective, cognitive, and sociocultural ones. Bullying is a multidimensional and social construction that feeds on the culture of fear, manifested in physical or psychological abuse, ownership or control, and an asymmetrical expression of power during social interactions that take place within or outside educational spaces. In conclusion, we all have a degree of responsibility on bullying, on knowing how to live and coexist free of violence, on the practice of healthy living at home, on education based on respect, and finally on the obligation to report all forms of abuse or bullying. The fundamental thing is to build respectful, supportive, and inclusive environments from a community approach.